2019
DOI: 10.1007/s00477-019-01694-y
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological post-processing based on approximate Bayesian computation (ABC)

Abstract: This study introduces a method to quantify the conditional predictive uncertainty in hydrological post-processing contexts when it is cumbersome to calculate the likelihood (intractable likelihood). Sometimes, it can be difficult to calculate the likelihood itself in hydrological modelling, specially working with complex models or with ungauged catchments. Therefore, we propose the ABC post-processor that exchanges the requirement of calculating the likelihood function by the use of some sufficient summary sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 80 publications
1
4
0
Order By: Relevance
“…This relative reduced performance of post-processing can be attributed to the satisfactory predictions of the GR4J model. This finding is consistent with previous results obtained by Romero-Cuellar et al (2019), who found that NSE increases by 25.84% post-processed poor predictions and 1.8% post-processed good predictions. Besides Ye et al (2014), Bogner et al (2016) and Woldemeskel et al (2018) confirmed that post-processing methods could improve forecast significantly when uncorrected predictions are exceptionally poor.…”
Section: Comparison Of Uncorrected and Post-processed Streamflow Predsupporting
confidence: 93%
See 3 more Smart Citations
“…This relative reduced performance of post-processing can be attributed to the satisfactory predictions of the GR4J model. This finding is consistent with previous results obtained by Romero-Cuellar et al (2019), who found that NSE increases by 25.84% post-processed poor predictions and 1.8% post-processed good predictions. Besides Ye et al (2014), Bogner et al (2016) and Woldemeskel et al (2018) confirmed that post-processing methods could improve forecast significantly when uncorrected predictions are exceptionally poor.…”
Section: Comparison Of Uncorrected and Post-processed Streamflow Predsupporting
confidence: 93%
“…Bayesian computation and streamflow statistics. Romero-Cuellar et al (2019) developed the ABC post-processor for inferential problems with intractable likelihood (see chapter 2), previously unavailable in a closed form or by numerical derivation (Robert, 2016). As the predictive uncertainty of climate change projections cannot be assessed by observations, but by summary statistics of observations, e.g.…”
Section: Jonathan Romero Cuéllarmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximate Bayesian Computation (ABC) is a widely utilized approach for simulation-based inference (Marin et al, 2012;Romero-Cuellar and Franceś, 2023). In ABC, the simulator generates synthetic data by sampling parameters from a prior distribution or proposal distribution and using these parameters to perform a simulation.…”
Section: Simulation-based Inferencementioning
confidence: 99%